2011
DOI: 10.3402/fnr.v55i0.6037
|View full text |Cite
|
Sign up to set email alerts
|

Indications for percutaneous endoscopic gastrostomy and survival in old adults

Abstract: BackgroundMany diseases striking old adults result in eating difficulties. Indications for selecting individuals for percutaneous endoscopic gastrostomy (PEG) are unclear and everybody may not benefit from the procedure.ObjectiveThe aim of this study was to evaluate indications for and survival after PEG insertion in patients older than 65 years.Design and MethodsA retrospective analysis including age, gender, diagnosis, indication, and date of death was made in 201 consecutive individuals, 94 male, mean age 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 25 publications
0
47
1
Order By: Relevance
“…It is proven to be associated with less complications and better nutritional outcomes than naso-gastric tube feeding (6). Common indications for PEG tube placement include swallowing difficulties caused by stroke, dementia, Parkinson’s disease, cancer or neurodegenerative diseases like amyotrophic lateral sclerosis (3,7,8,9,10). Short-term advantages of PEG tube include provision of nutrition, hydration, administration of medications, prolonged survival with improved quality of life (1,4,5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is proven to be associated with less complications and better nutritional outcomes than naso-gastric tube feeding (6). Common indications for PEG tube placement include swallowing difficulties caused by stroke, dementia, Parkinson’s disease, cancer or neurodegenerative diseases like amyotrophic lateral sclerosis (3,7,8,9,10). Short-term advantages of PEG tube include provision of nutrition, hydration, administration of medications, prolonged survival with improved quality of life (1,4,5).…”
Section: Discussionmentioning
confidence: 99%
“…In a study performed by Malmgren et al that studied indications for PEG-tube placement and survival in older adults, it was noted that patients over the age of 80 years, especially those with cognitive dysfunction, had slightly worse prognosis than younger patients. However, the limitation of this study was that the investigators did not report the baseline cognitive status in these patients at the time of PEG-tube placement (8), which would likely be an important determinant of PEG success. The overall 30-day mortality was 22% and 1-year mortality was 50% in a study by Callahan et al , reporting on the outcomes of PEG tube placement in elderly community dwellers (9), and these numbers have been corroborated by other studies (25, 26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Moreover, several studies reported a high 30-day mortality rate after placement of a PEG tube. 5 Therefore, it is critical to find clinical variables that may affect the decision-making and identify the patients that may benefit most from the procedure.…”
Section: Dear Editormentioning
confidence: 99%
“…29 Although large prospective studies have examined outcomes of PEG feeding in patients with dementia, a Cochrane review showed no evidence of increased survival, reduced pressure ulcers, or improved quality of life, nutritional status, function, behaviour, or psychiatric symptoms of dementia in patients with advanced dementia who were fed using gastrostomy tubes. 30 Moreover, some studies reported a high 30-day mortality rate (22%) after PEG placement in elderly patients, 31 and a 30% mortality rate during hospital stay in inpatients undergoing PEG. 32 For these reasons, many authors claim that PEG is not indicated in severe dementia, 30 and should be cautiously pondered in patients older than eighty years with moderate dementia.…”
Section: 19mentioning
confidence: 99%